PERILAKU PENUTUR BAHASA TOBELO PADA MASYARAKAT DI DESA KUMO, KECEMATAN TOBELO KABUPATEN HALMAHERA UTARA - Badjo, Charles; Mawara, Jetty E. T.; Deeng, Djefry (Universitas Sam Ratulangi, 2021)
Language is one of the cultural elements that is a system of speech sounds that are used to communicate by the people who use it. Regional languages are the most prominent distinguishing feature because with the language of each social group or local community feel themselves as a different unity from other groupsThe behavior of speakers is very important and more especially in the Tobelo regional language to young people as the next generation, and it is very important to be explored and developed in the process of social interaction of the community, because some parents and local village governments do not pay attention anymore, so that they as children or as the next generation must continue to learn and develop the Tobelo regional language, so that the language of the Tobelo region / language of the ancestors does not just disappear and can be developed by the younger generation. The behavior of speakers in more dominant communities using Tobelo regional languages to communicate daily is parents compared to young people, this is quite reasonable for parents in Kumo village who are more mastery of Tobelo regional language, both verbally and in writing. The younger generation view that regional languages are less prestigious or rural, but other languages (e.g., Indonesian, or other dominant languages) are considered more prestigious than their local languages.Â Keywords: speakers, spoken, regional language